The Effect of Dutch Disease on Trade Openness and Foreign Direct Investment in Algeria - BOUSSALEM, Soufiane; BENTERKI, Azzedine (Journal of Human Sciences, 2015)
This study aims to explain the poor performance of trade openness and foreign direct investment recorded in Algeria the last few years. The period of the study extends from 2004 to 2013. Using a time series data type, a classic linear regression model has been adopted in order to test hypotheses and explain the relationship between natural resource dependence and the performance of trade openness and foreign direct investment. SPSS software for windows version 19 has been used for statistical analysis which revealed several findings, essentially that there is a negative relationship between natural resource dependence and trade openness and foreign direct investment performances, which means that an increase of resource dependence results in a decrease in both trade openness and foreign direct investment.